Electrode for secondary battery, secondary battery including the same, and method for manufacturing the electrode
The development of a secondary battery electrode using a dry method with a specific binder composition and shear force application addresses the challenges of high-temperature processing, resulting in improved strength and reduced resistance for enhanced battery performance.
Patent Information
- Application Number
- JP2023523638
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-15
- Filing Date
- 2021-10-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-10-19
AI Technical Summary
Existing secondary battery electrodes manufactured by wet methods require high-temperature heat treatment, which can damage metal oxides and necessitate the development of dry method electrodes with improved strength and reduced resistance.
A secondary battery electrode composed of an electrode current collector with an electrode layer made from a dry mixture of an active material, conductive material, a first binder with a higher molecular weight, and a second binder with a lower molecular weight, applied using a shear force to create a free-standing film with enhanced tensile strength and reduced resistance.
The proposed electrode manufacturing method improves the tensile strength and reduces the resistance of secondary battery electrodes, enhancing their performance and durability while avoiding the risks associated with high-temperature processing.
Smart Images

Figure 0007667263000004 
Figure 0007667263000005 
Figure 0007667263000006
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0137054 filed on October 21, 2020, and Korean Patent Application No. 10-2021-0137263 filed on October 15, 2021, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to an electrode for a secondary battery, a secondary battery including the same, and a method for manufacturing the electrode, and more particularly to an electrode for a secondary battery having improved strength and resistance reducing effect, a secondary battery including the same, and a method for manufacturing the electrode. [Background technology]
[0003] Along with technological development and increasing demand for mobile devices, the demand for secondary batteries as an energy source is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.
[0004] In particular, secondary batteries have attracted great attention as energy sources for power plants such as electric bicycles, electric vehicles, and hybrid electric vehicles, as well as for mobile devices such as mobile phones, digital cameras, notebook computers, and wearable devices.
[0005] In addition, with the growing interest in environmental issues, much research is being conducted on electric vehicles and hybrid electric vehicles that can replace vehicles that use fossil fuels such as gasoline vehicles and diesel vehicles, which are one of the main causes of air pollution. Nickel metal hydride secondary batteries are mainly used as the power source for such electric vehicles and hybrid electric vehicles, but active research is being conducted on the use of lithium secondary batteries with high energy density and discharge voltage, and some of them are already in the commercialization stage.
[0006] Existing secondary battery electrodes have generally been manufactured using a wet process. However, when manufacturing electrodes using a wet process, a heat treatment process at high temperatures is required, which may damage the metal oxide. Therefore, there is an increasing need to develop electrodes manufactured using a dry process. Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide an electrode for a secondary battery having improved tensile strength and resistance reducing effect, a secondary battery including the same, and a method for manufacturing the electrode.
[0008] The problems to be solved by the present invention are not limited to the problems described above, and problems not mentioned will be clearly understood by a person having ordinary skill in the art to which the present invention pertains from this specification and the accompanying drawings. [Means for solving the problem]
[0009] According to one embodiment of the present invention, there is provided an electrode for a secondary battery, comprising: an electrode current collector; and an electrode layer disposed on the electrode current collector, the electrode layer comprising an electrode composition in which an active material, a conductive material, a first binder, and a second binder are dry-mixed, and a molecular weight calculated from an SSG value of the first binder is greater than a molecular weight calculated from an SSG value of the second binder.
[0010] The first binder has an SSG (Specific Standard Gravity) value of 2.0 to 2.169, and the second binder has an SSG value of 2.171 to 2.2, and the SSG value can be expressed by the following Equation 1. SSG = 2.612 - 0.58 × log(M x )(M x = molecular weight of x) (Equation 1)
[0011] The total content of the first binder and the second binder may be 1.01 wt % or more and 11.99 wt % or less based on the total weight of the electrode composition.
[0012] The content ratio of the first binder to the second binder may be in the range of 1:10 to 10:1.
[0013] The secondary battery electrode may have a contact angle deviation of 0.01 degrees or more and 5.0 degrees or less.
[0014] The first binder and the second binder may each contain polytetrafluoroethylene (PTFE).
[0015] The active material may include at least one of lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium copper oxide (Li2CuO2), vanadium oxide, Ni-site type lithium nickel oxide, lithium manganese composite oxide, lithium manganese composite oxide having a spinel structure, LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion, a disulfide compound, Fe2(MoO4)3, and lithium manganese oxide (LMO, lithium manganese oxide).
[0016] The electrode composition may be fabricated into a free-standing film, and the free-standing film may be adhered onto the electrode current collector.
[0017] The free-standing film has a strength of 8kgf / cm 2 More than 40kgf / cm 2 It may have the following tensile strength:
[0018] According to another embodiment of the present invention, a method for manufacturing an electrode for a secondary battery includes the steps of: dry-mixing an active material, a conductive material, a first binder, and a second binder to prepare a mixture; applying a shear force to the mixture to prepare an electrode composition; preparing a free-standing film from the electrode composition; and attaching the free-standing film onto an electrode current collector to form an electrode for a secondary battery, wherein a molecular weight calculated from an SSG value of the first binder is greater than a molecular weight calculated from an SSG value of the second binder.
[0019] The first binder has an SSG (Specific Standard Gravity) value of 2.0 to 2.169, and the second binder has an SSG value of 2.171 to 2.2, and the SSG value can be expressed by the following Equation 1. SSG = 2.612 - 0.58 × log(M x )(M x = molecular weight of x) (Equation 1)
[0020] The total content of the first binder and the second binder may be 1.01 wt % or more and 11.99 wt % or less based on the total weight of the electrode composition.
[0021] The content ratio of the first binder to the second binder may be in the range of 1:10 to 10:1.
[0022] The secondary battery electrode may have a contact angle deviation of 0.01 to 5.0.
[0023] The first binder and the second binder may each contain polytetrafluoroethylene (PTFE).
[0024] The active material may include at least one of lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium copper oxide (Li2CuO2), vanadium oxide, Ni-site type lithium nickel oxide, lithium manganese composite oxide, lithium manganese composite oxide having a spinel structure, LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion, a disulfide compound, Fe2(MoO4)3, and lithium manganese oxide (LMO, lithium manganese oxide).
[0025] A secondary battery according to another embodiment of the present invention may include the above-described secondary battery electrode. Effect of the Invention
[0026] According to an embodiment of the present invention, by manufacturing an electrode for a secondary battery and a secondary battery including the same using an electrode composition including binders having molecular weights calculated from different SSG values, the strength of the electrode can be improved and the resistance reduction effect of the secondary battery including the electrode can be improved.
[0027] The effects of the present invention are not limited to the effects described above, and effects not mentioned will be clearly understood by those having ordinary skill in the art to which the present invention pertains from this specification and the accompanying drawings. [Brief description of the drawings]
[0028] [Figure 1] 2 is a flowchart illustrating a method for manufacturing an electrode for a secondary battery according to an embodiment of the present invention. [Diagram 2] 1 is a graph comparing tensile strength, contact angle deviation, and initial discharge capacity according to the molecular weight calculated from the SSG value of a binder in an electrode for a secondary battery in an embodiment of the present invention and a comparative example. [Diagram 3] 4 is a graph comparing tensile strength, contact angle deviation, and initial discharge capacity according to the binder content of a secondary battery electrode in Examples and Comparative Examples of the present invention. [Figure 4] 4 is a graph comparing tensile strength, contact angle deviation, and initial discharge capacity according to the content ratio of a first binder and a second binder in a secondary battery electrode in Examples and Comparative Examples of the present invention. [Diagram 5] 1 is a graph comparing tensile strength, contact angle deviation, and initial discharge capacity according to the molecular weight calculated from the SSG value of a second binder of an electrode for a secondary battery in an embodiment of the present invention and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the embodiments set forth herein.
[0030] Hereinafter, an electrode for a secondary battery according to one embodiment of the present invention will be described.
[0031] An electrode for a secondary battery according to an embodiment of the present invention includes an electrode current collector, and an electrode layer formed as a free standing film on the electrode current collector, the electrode layer including an electrode composition in which an active material, a conductive material, a first binder, and a second binder are dry-mixed.
[0032] The electrode layer may be formed by first preparing a free-standing film, attaching the free-standing film to the electrode current collector, and then performing a lamination process. Here, the free-standing film has a strength of 8 kgf / cm 2 More than 40kgf / cm 2 It may have the following tensile strength:
[0033] Therefore, the freestanding film may be in a state in which the active material, conductive material, first binder, and second binder contained in the electrode composition are mixed with each other with high binding strength, and the freestanding film may be easily stored in a roll form. Therefore, the productivity may be improved and the flexibility of the electrode may be effectively improved. However, the tensile strength of the freestanding film is 8 kgf / cm 2 If the electrode active material is less than this, cracks may occur between the electrode active materials in the electrode during charging and discharging, resulting in a problem of reduced life characteristics.
[0034] In addition, the secondary battery electrode may have a contact angle deviation of 0.01 degrees or more and 5.0 degrees or less. More preferably, the secondary battery electrode may have a contact angle deviation of 0.05 degrees or more and 4.0 degrees or less. As an example, the secondary battery electrode may have a contact angle deviation of 0.1 degrees or more and 3.0 degrees or less. Here, the contact angle may refer to the average and standard deviation of the contact angles at each corner and the center of the electrode surface.
[0035] Therefore, the secondary battery electrode has a small deviation in contact angle, so that the dispersibility of the binder contained in the electrode composition can be improved, and the bridging effect of the binder can be excellent, so that the electrode including the electrode composition can have an excellent resistance reducing effect.
[0036] However, when the contact angle deviation of the secondary battery electrode exceeds 5.0 degrees, the contact angle deviation becomes large, and the dispersibility of the binder contained in the electrode composition may decrease, and the bridging effect of the binder may decrease, so that the resistance of the electrode containing the electrode composition may be high, and the discharge capacity of the battery cell may also decrease.
[0037] Hereinafter, each component included in an electrode for a secondary battery according to an embodiment of the present invention will be described in detail.
[0038] The electrode for a secondary battery according to the present embodiment may include the first binder and the second binder as binders. Here, the first binder and the second binder serve to improve adhesion between active material particles and adhesion between the active material and the current collector, respectively. Specific examples include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination.
[0039] As an example, each of the first binder and the second binder may include polytetrafluoroethylene (PTFE). Here, polytetrafluoroethylene (PTFE) has a characteristic that fibers are pulled out from particles by application of shear force. That is, in the electrode for a secondary battery according to an embodiment of the present invention, a strong shear force is applied to an electrode composition including polytetrafluoroethylene (PTFE) as a first binder and a second binder, respectively, and the electrode composition may be mixed by a physical mixing method by fiberization of polytetrafluoroethylene (PTFE).
[0040] To this end, in the electrode for a secondary battery according to an embodiment of the present invention, the electrode composition may be mixed in a dry manner without a separate solvent or additive, which is very effective in bridging between active material particles or between the active material particles and a current collector, and damage to the active material that may occur during a heat treatment at high temperatures in a conventional mixing method may be prevented.
[0041] Here, polytetrafluoroethylene (PTFE) forms fibers by extending the CF2-CF2 chain contained in polytetrafluoroethylene (PTFE), and this characteristic can be greatly influenced by the molecular weight of polytetrafluoroethylene (PTFE). However, polytetrafluoroethylene (PTFE) is chemically very stable, and it is difficult to measure the molecular weight by the conventionally known method, so the molecular weight can be measured by calculating the SSG (Specific Standard Gravity) value as shown in the following Equation 1. SSG = 2.612 - 0.58 × log(M x )(M x = molecular weight of x) (Equation 1)
[0042] Here, the SSG value may be measured by ASTM D1457, ASTM D4895, etc. However, the present embodiment is not limited to these, and any measurement method capable of measuring the SSG value of polytetrafluoroethylene (PTFE) may be included in the present embodiment.
[0043] In the electrode for a secondary battery according to an embodiment of the present invention, the molecular weight calculated from the SSG value of the first binder is greater than the molecular weight calculated from the SSG value of the second binder. In other words, the molecular weight calculated from the SSG value of the first binder may be similar to or greater than the molecular weight of conventional polytetrafluoroethylene (PTFE), and the molecular weight calculated from the SSG value of the second binder may be similar to or smaller than the molecular weight of conventional polytetrafluoroethylene (PTFE).
[0044] Based on the SSG value according to the above-mentioned mathematical formula 1, the molecular weight of conventional polytetrafluoroethylene (PTFE) falls within the range of SSG value of 2.160 to 2.180. In addition, when the SSG value of polytetrafluoroethylene (PTFE) is greater than 2.210, that is, polytetrafluoroethylene (PTFE) having an excessively low molecular weight, is generally difficult to be fiberized.
[0045] Here, the SSG value of the first binder may be 2.0 or more and 2.169 or less, and the SSG value of the second binder may be 2.171 or more and 2.2 or less. More preferably, the SSG value of the first binder may be 2.05 or more and 2.165 or less, and the SSG value of the second binder may be 2.175 or more and 2.2 or less. For example, the SSG value of the first binder may be 2.1 or more and 2.16 or less, and the SSG value of the second binder may be 2.180 or more and 2.2 or less.
[0046] Therefore, the electrode for a secondary battery according to the present embodiment may have excellent tensile strength because the binder includes the first binder having a relatively high molecular weight calculated from the SSG value, thereby maximizing the fiberization of the binder and providing excellent bridging effect between particles within the electrode composition. Furthermore, the binder includes the second binder having a relatively low molecular weight calculated from the SSG value, thereby preventing the binder from agglomerating and improving dispersibility, thereby providing excellent resistance reduction effect of an electrode including the electrode composition. In other words, the electrode for a secondary battery according to the present embodiment may have excellent resistance reduction effect of an electrode while improving strength.
[0047] On the other hand, when the SSG values of the first binder and the second binder are out of the above range and fall within the range of 2.160 to 2.180, at least a portion of the first binder and the second binder may be fiberized together, causing a problem of agglomeration. Such agglomeration may reduce interparticle dispersion in the electrode slurry, and the resistance reduction effect of the electrode including the electrode composition may be reduced.
[0048] In addition, if the first and second binders have an SSG value that is too small beyond the above range, the first and second binders may be excessively agglomerated, and the bridging effect between the active material particles and the binder may be reduced. In addition, if the first and second binders have an SSG value that is too large beyond the above range, the first and second binders may not be sufficiently fibrillated, and the tensile strength may be reduced.
[0049] In addition, the total content of the first binder and the second binder may be 1.01 wt% or more and 11.99 wt% or less based on the total weight of the electrode composition. More preferably, the total content of the first binder and the second binder may be 1.5 wt% or more and 11 wt% or less based on the total weight of the electrode composition. As an example, the total content of the first binder and the second binder may be 2 wt% or more and 10 wt% or less based on the total weight of the electrode composition.
[0050] For this reason, the secondary battery electrode according to the present embodiment includes the first binder and the second binder in the ratio within the above-mentioned range, so that the fiberization of the binder can be maximized, and the bridging effect between particles in the electrode composition can be excellent, so that the electrode can have excellent tensile strength. Furthermore, the aggregation phenomenon of the binder can be prevented and the dispersibility can be improved, so that the electrode including the electrode composition can have an excellent resistance reduction effect.
[0051] On the other hand, if the total content of the first binder and the second binder is less than 1.01% by weight, the bridging effect between particles in the electrode composition may decrease, and the tensile strength may also decrease significantly. Also, if the total content of the first binder and the second binder is more than 11.99% by weight, the first binder and the second binder act as resistors in an electrode containing the electrode composition, making it difficult to expect high output.
[0052] In addition, the content ratio of the first binder to the second binder may be 0.1:10 to 10:0.1. More preferably, the content ratio of the first binder to the second binder may be 0.5:10 to 10:0.5. As an example, the content ratio of the first binder to the second binder may be 1:10 to 10:1.
[0053] For this reason, the secondary battery electrode according to the present embodiment includes the first binder and the second binder in the ratio within the above-mentioned range, so that the fiberization of the binder can be maximized, and the bridging effect between particles in the electrode composition can be excellent, so that the electrode composition can have excellent tensile strength. Furthermore, the electrode composition can have excellent resistance reduction effect by preventing the aggregation phenomenon of the binder and improving dispersibility.
[0054] On the other hand, when the content ratio of the first binder to the second binder is less than 0.1:more than 10, the degree of fiberization of the binder may decrease and the tensile strength may decrease significantly. Also, when the content ratio of the first binder to the second binder is more than 10:less than 0.1, aggregation of the binder often occurs, which may decrease the interparticle dispersion within the electrode composition and decrease the resistance reduction effect of the electrode including the electrode composition.
[0055] The active material may be a positive electrode active material, and examples of the positive electrode active material include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide, lithium copper oxide (Li2CuO2), vanadium oxide, Ni-site type lithium nickel oxide, lithium manganese composite oxide, lithium manganese composite oxide with spinel structure, LiMn2O4 in which part of Li in the chemical formula is replaced with an alkaline earth metal ion, disulfide compound, Fe2(MoO4)3, and the like.
[0056] For example, the active material may include lithium manganese oxide (LMO). Here, the active material may be included in an amount of 85 wt% to 99 wt% based on the total weight of the electrode composition. More preferably, the active material may be included in an amount of 87 wt% to 98 wt% based on the total weight of the electrode composition. For example, the active material may be included in an amount of 89 wt% to 97 wt% based on the total weight of the electrode composition.
[0057] The conductive material is used to impart conductivity to the electrode, and can be used without any particular restrictions as long as it does not cause chemical changes in the battery that is constructed but has electronic conductivity. Specific examples include carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, graphene, and carbon fiber; graphite such as natural graphite and artificial graphite; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one or more of these can be used alone or in combination. Here, the conductive material can be included in an amount of 1% by weight to 10% by weight based on the total weight of the electrode.
[0058] The above-described secondary battery electrode may be included as a positive electrode in a secondary battery according to another embodiment of the present invention. More specifically, the secondary battery according to another embodiment of the present invention may include an electrode assembly including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, and an electrolyte.
[0059] The negative electrode may be prepared by coating a negative electrode current collector with a negative electrode slurry containing a negative electrode active material, a polymer material, a conductive material, and the like, as in the case of the secondary battery electrode.
[0060] The negative electrode may also be prepared in such a manner that a negative electrode slurry including a negative electrode active material is attached or coated on a negative electrode current collector, and the negative electrode slurry may further include a conductive material and a polymer material as described above, in addition to the negative electrode active material.
[0061] The negative electrode active material may be a negative electrode active material commonly used in the art for lithium secondary batteries, such as lithium metal, lithium alloy, petroleum coke, activated carbon, graphite, silicon, tin, metal oxides, or other carbons.
[0062] The negative electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like, aluminum-cadmium alloy, or the like can be used. The separator serves to separate the negative electrode and the positive electrode and to provide a passage for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, a separator that has low resistance to the movement of electrolyte ions and excellent electrolyte humidification ability is preferred.
[0063] In addition, examples of the electrolyte solution used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.
[0064] Specifically, the electrolyte may include an organic solvent and a lithium salt. The organic solvent may be any organic solvent that can act as a medium through which ions involved in the electrochemical reaction of the battery can move. The lithium salt may be any lithium salt that can provide lithium ions used in the lithium secondary battery.
[0065] In addition to the above-mentioned components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphate, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in the battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 wt % to 5 wt % based on the total weight of the electrolyte.
[0066] 1 is a flow chart of a method for manufacturing an electrode for a secondary battery according to an embodiment of the present invention. Referring to FIG 1, the method for manufacturing an electrode according to the present embodiment includes a premixing step (S10) of mixing an active material, a conductive material, and a binder, a mixing step (S20) of manufacturing an electrode composition by applying high shear force, a step (S30) of manufacturing a free-standing film using the electrode composition, and a step (S40) of manufacturing an electrode through a lamination process after attaching the free-standing film onto an electrode current collector.
[0067] In the premixing step (S10), the active material, the conductive material, and the binder may be mixed in a dry state, and the molecular weight calculated from the SSG value of the first binder may be greater than the molecular weight calculated from the SSG value of the second binder.
[0068] The present invention will be described below with reference to more specific examples. However, the following examples are provided to illustrate the present invention and are not intended to limit the scope of the present invention.
[0069] <Example 1> A premixing step is performed to prepare a mixture by dry mixing the active material, conductive material, first binder, and second binder using a blender facility manufactured by Waring Co. Here, the active material is 90 wt% lithium manganese oxide (LMO), and the conductive material is 2 wt% Super C65. The first binder contains 4 wt% polytetrafluoroethylene (PTFE) having an SSG value of 2.156, and the second binder contains 4 wt% polytetrafluoroethylene (PTFE) having an SSG value of 2.186. At this time, the premixing step (S10) is performed at 5000 rpm for 1 minute. Then, a mixing step (S20) is performed at 30 rpm for 5 minutes using PBV-0.1L facility manufactured by Irie Shokai Co. to apply shear force to the mixture prepared in the premixing step (S10) to prepare an electrode composition.
[0070] <Example 2> In Example 1, the active material was 96 wt % lithium manganese oxide (LMO), the first binder was 1 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.156, and the second binder was 1 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.186. Except for this, an electrode composition was prepared in the same manner as in Example 1.
[0071] <Example 3> In Example 1, the first binder contained 7 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.156, and the second binder contained 1 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.186. Except for this, an electrode composition was prepared in the same manner as in Example 1.
[0072] <Example 4> In Example 1, the first binder contained 1 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.156, and the second binder contained 7 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.186. Except for this, an electrode composition was prepared in the same manner as in Example 1.
[0073] <Comparative Example 1> In Example 1, the first binder contained 0 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.156, and the second binder contained 8 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.186. Except for this, an electrode composition was prepared in the same manner as in Example 1.
[0074] <Comparative Example 2> In Example 1, the first binder contained 8 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.156, and the second binder contained 0 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.186. Except for this, an electrode composition was prepared in the same manner as in Example 1.
[0075] <Comparative Example 3> In Example 1, the first binder contained 4 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.156, and the second binder contained 4 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.17. Except for this, an electrode composition was prepared in the same manner as in Example 1.
[0076] <Comparative Example 4> In Example 1, the first binder contained 4 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.17, and the second binder contained 4 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.186. Except for this, an electrode composition was prepared in the same manner as in Example 1.
[0077] <Comparative Example 5> In Example 1, the active material was 97 wt % lithium manganese oxide (LMO), the first binder was 0.5 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.156, and the second binder was 0.5 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.186. Except for this, an electrode composition was prepared in the same manner as in Example 1.
[0078] <Comparative Example 6> In Example 1, the active material was 86 wt % lithium manganese oxide (LMO), the first binder was 6 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.156, and the second binder was 6 wt % polytetrafluoroethylene (PTFE) having an SSG value of 2.186. Except for this, an electrode composition was prepared in the same manner as in Example 1.
[0079] <Comparative Example 7> In Example 1, the second binder includes polytetrafluoroethylene (PTFE) having an SSG value of 2.237. Except for this, an electrode composition was prepared in the same manner as in Example 1.
[0080] <Experimental Example 1 (Measurement of Tensile Strength)> The electrode compositions prepared in Examples 1 to 4 and Comparative Examples 1 to 7 were subjected to a free-standing film preparation step (S30) in which a free-standing film having a length of 20 mm and a width of 20 mm was prepared using a roll mill facility manufactured by Inoue Manufacturing Co., Ltd. Both ends of each of the prepared free-standing films were fixed with a jig, and the tensile strength of each of the free-standing films was measured at a speed of 50 mm / min using a UTM facility manufactured by Instron Co., Ltd. The results are shown in Table 1.
[0081] [Table 1]
[0082] <Experimental Example 2 (Contact Angle Measurement)> For Examples 1 to 4 and Comparative Examples 1 to 7, the free-standing films produced in Experimental Example 1 were roll-pressed onto a current collector made of aluminum foil, and then the loading value was 5 mAh / cm 2 The electrode fabrication step (S40) was carried out to fabricate a positive electrode with a porosity of 30%. Then, for each of the fabricated electrodes, a 5cm x 5cm sample was randomly taken, and 200μl of distilled water was dropped on each corner and the center, a total of five locations, to measure the contact angle, and the average and standard deviation were calculated. The results are shown in Table 2.
[0083] [Table 2]
[0084] <Experimental Example 3 (Measurement of Discharge Capacity)> For Examples 1 to 4 and Comparative Examples 1 to 7, coin half cells were manufactured using a lithium metal having a thickness of 200 μm as the negative electrode together with the positive electrode manufactured in Experimental Example 2. Then, each manufactured coin half cell was charged and discharged at 0.1 C / 0.1 C in the voltage range of 3.0 to 4.3 V, and the discharge capacity value of the first cycle was calculated, and the results are shown in Table 3.
[0085] [Table 3]
[0086] <Analysis of Experimental Results> Fig. 2 is a graph comparing the tensile strength, contact angle deviation, and initial discharge capacity according to the molecular weight calculated from the SSG value of the binder of the secondary battery electrode according to the embodiment and the comparative example of the present invention. In particular, Fig. 2 is a graph comparing the tensile strength, contact angle deviation, and initial discharge capacity of Example 1, Comparative Example 3, and Comparative Example 4 among the results shown in Tables 1 to 3. Here, Example 1, Comparative Example 3, and Comparative Example 4 have the same contents and content ratios of the first binder and the second binder, but the SSG value of the first binder and the SSG value of the second binder are different.
[0087] In the case of Comparative Example 3, the SSG value of the second binder was 2.17, which was a smaller SSG value than those of the Examples, and in the case of Comparative Example 4, the SSG value of the first binder was 2.17, which was a larger SSG value than those of the Examples.
[0088] 2, Comparative Example 3 has excellent tensile strength, but has a large deviation in contact angle and a small initial discharge capacity, unlike Examples 1 and 4. That is, when a second binder having a smaller SSG value than the Examples is included, it can be seen that the aggregation phenomenon of the first and second binders themselves increases compared to Example 1, resulting in a decrease in initial discharge capacity and dispersibility.
[0089] In addition, it can be confirmed that Comparative Example 4 has an excellent initial discharge capacity, but has a low tensile strength, unlike Example 1 and Comparative Example 3. In other words, when the first binder having a larger SSG value is included compared to the examples, the molecular weight calculated from the SSG value of the first binder is smaller than that of Example 1, fiberization is not sufficiently performed, and the tensile strength is also reduced.
[0090] Therefore, when the first binder and the second binder having the SSG values as in Example 1 are included, it can be confirmed that the tensile strength is excellent, the dispersibility due to contact angle deviation and the initial discharge capacity are all generally excellent, and the resistance reduction effect is also excellent.
[0091] Fig. 3 is a graph comparing the tensile strength, contact angle deviation, and initial discharge capacity depending on the binder content of secondary battery electrodes according to the examples and comparative examples of the present invention. In particular, Fig. 3 is a graph comparing the tensile strength, contact angle deviation, and initial discharge capacity of Example 1, Example 2, Comparative Example 5, and Comparative Example 6 among the results shown in Tables 1 to 3. Here, Example 1, Example 2, Comparative Example 5, and Comparative Example 6 have the same content ratio of the first binder and the second binder, but different total contents.
[0092] In the order of Comparative Example 5, Example 2, Example 1, and Comparative Example 6, the total content of the first binder and the second binder increases to 1 wt %, 2 wt %, 8 wt %, and 12 wt %.
[0093] 3, as the total content of the first binder and the second binder increases, the tensile strength is excellent, the contact angle deviation is decreased, and the dispersibility is improved. However, the initial discharge capacity is decreased. That is, if the total content of the first binder and the second binder is too small, the tensile strength and dispersibility are decreased. Also, if the total content of the first binder and the second binder is too large, the resistance of the binder increases due to the increase in the binder content, and the initial discharge capacity is decreased.
[0094] Therefore, when the total content of the first binder and the second binder is as in Examples 1 and 2, it can be confirmed that the tensile strength is excellent, the dispersibility based on the contact angle deviation and the initial discharge capacity are all generally excellent, and the resistance reduction effect is also excellent.
[0095] Fig. 4 is a graph comparing the tensile strength, contact angle deviation, and initial discharge capacity according to the content ratio of the first binder and the second binder of secondary battery electrodes according to examples and comparative examples of the present invention. In particular, Fig. 4 is a graph comparing the tensile strength, contact angle deviation, and initial discharge capacity of Example 3, Example 4, Comparative Example 1, and Comparative Example 2 among the results shown in Tables 1 to 3. Here, the contents of the first binder and the second binder are the same at 8 wt % in Example 3, Example 4, Comparative Example 1, and Comparative Example 2, but the content ratios are different from each other.
[0096] In the case of Comparative Example 2, it contains 8 wt% of the first binder and 0 wt% of the second binder, in the case of Example 3, it contains 7 wt% of the first binder and 1 wt% of the second binder, in the case of Example 4, it contains 1 wt% of the first binder and 7 wt% of the second binder, and in the case of Comparative Example 1, it contains 0 wt% of the first binder and 8 wt% of the second binder.
[0097] 4, Comparative Example 2 has excellent tensile strength, but a large deviation in contact angle and a small initial discharge capacity. Comparative Example 1 has excellent initial discharge capacity and a small deviation in contact angle, but a low tensile strength. That is, it can be seen that the initial discharge capacity and dispersibility decrease as the content of the first binder, which has a relatively large molecular weight calculated from the SSG value, increases. Conversely, it can be seen that the tensile strength decreases as the content of the second binder, which has a relatively small molecular weight calculated from the SSG value, increases.
[0098] Therefore, when the content ratio of the first binder and the second binder is included as in Examples 3 and 4, it can be confirmed that the tensile strength is excellent, the dispersibility due to contact angle deviation and the initial discharge capacity are all generally excellent, and the resistance reduction effect is also excellent.
[0099] Fig. 5 is a graph comparing the tensile strength, contact angle deviation, and initial discharge capacity according to the molecular weight calculated from the SSG value of the second binder of the electrode for a secondary battery in the examples and comparative examples of the present invention. In particular, Fig. 5 is a graph comparing the tensile strength, contact angle deviation, and initial discharge capacity of Example 1, Comparative Example 3, and Comparative Example 7 among the results shown in Tables 1 to 3. Here, Example 1, Comparative Example 3, and Comparative Example 7 have the same content of the first binder and the second binder, each of which is 4 wt %, but the SSG value of the second binder is different from each other.
[0100] In the case of Comparative Example 3, the SSG value of the second binder is 2.17, which is smaller than that of the Examples, and in the case of Comparative Example 7, the SSG value of the second binder is 2.237, which is larger than that of the Examples.
[0101] 5, Comparative Example 3 has excellent tensile strength, but has a large deviation in contact angle and a small initial discharge capacity, unlike Example 1. That is, when a second binder having a smaller SSG value is included compared to the Examples, the second binder is also excessively fibrous, and the aggregation phenomenon of the first binder and the second binder itself increases compared to Example 1, resulting in a decrease in initial discharge capacity and dispersibility.
[0102] In addition, it can be seen that Comparative Example 7 has low tensile strength and initial discharge capacity, and also has a large contact angle deviation, unlike Example 1. That is, when the second binder having a large SSG value is included compared to the examples, it can be seen that the second binder is not well fiberized, and the results are similar to those when only the first binder is included as in Comparative Example 2. That is, it can be seen that the tensile strength, initial discharge capacity, and dispersibility are all lower in Comparative Example 7 compared to Example 1.
[0103] Therefore, when the second binder having the SSG value as in Example 1 is included, it can be confirmed that the tensile strength is excellent, the dispersibility due to contact angle deviation and the initial discharge capacity are all generally excellent, and the resistance reduction effect is also excellent.
[0104] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the claims also fall within the scope of the present invention.
Claims
1. An electrode current collector, and an electrode layer disposed on the electrode current collector; The electrode layer includes a dry mixed electrode composition of an active material, a conductive material, a first binder, and a second binder; The total content of the first binder and the second binder is 1.01 wt % or more and 11.99 wt % or less based on the total weight of the dry mixed electrode composition; The molecular weight calculated from the SSG value of the first binder is greater than the molecular weight calculated from the SSG value of the second binder; The first binder has an SSG value of 2.0 or more and 2.169 or less, and the second binder has an SSG value of 2.171 or more and 2.2 or less, The SSG value is expressed by the following Equation 1: SSG=2.612-0.58×log(M x ) (Formula 1) M x is the molecular weight of x, where x is the first binder or the second binder; The electrode for a secondary battery, wherein the first binder and the second binder each contain polytetrafluoroethylene (PTFE).
2. The electrode for a secondary battery according to claim 1 , wherein a content ratio of the first binder to the second binder is in the range of 1:10 to 10:
1.
3. 2. The electrode for a secondary battery according to claim 1, wherein the deviation of the contact angle of the electrode for a secondary battery is 0.01 degrees or more and 5.0 degrees or less.
4. The active material is lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), lithium copper oxide (Li 2 CuO 2 ), vanadium oxide, Ni-site type lithium nickel oxide, lithium manganese composite oxide, lithium manganese composite oxide with spinel structure, LiMn 2 O 4 , disulfide compound, Fe 2 (MoO 4 ) 3 2. The electrode for a secondary battery according to claim 1, comprising at least one of a lithium manganese oxide (LMO) and a lithium manganese oxide (LMO).
5. The dry mixed electrode composition is a free-standing film, 2. The electrode for a secondary battery according to claim 1, wherein the free-standing film is attached onto the electrode current collector.
6. The free-standing film has a strength of 8 kgf / cm 2 More than 40 kgf / cm 2 6. The electrode for a secondary battery according to claim 5, having a tensile strength of:
7. dry mixing an active material, a conductive material, a first binder, and a second binder to prepare a mixture; applying a shear force to the mixture to produce an electrode composition; preparing a free-standing film from the electrode composition; and The free-standing film is attached onto an electrode current collector to form an electrode for a secondary battery; The total content of the first binder and the second binder is 1.01 wt % or more and 11.99 wt % or less based on the total weight of the electrode composition, The molecular weight calculated from the SSG value of the first binder is greater than the molecular weight calculated from the SSG value of the second binder, The first binder has an SSG value of 2.0 or more and 2.169 or less, and the second binder has an SSG value of 2.171 or more and 2.2 or less, The SSG value is expressed by the following Equation 1: SSG=2.612-0.58×log(M x ) (Formula 1) M x is the molecular weight of x, where x is the first binder or the second binder; The method for manufacturing an electrode for a secondary battery, wherein the first binder and the second binder each contain polytetrafluoroethylene (PTFE).
8. 8. The method of claim 7, wherein a content ratio of the first binder to the second binder is in the range of 0.1:10 to 10:0.
1.
9. 8. The method for manufacturing an electrode for a secondary battery according to claim 7, wherein the electrode for a secondary battery has a deviation of a contact angle of 0.01 or more and 5.0 or less.
10. The active material is lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), lithium copper oxide (Li 2 CuO 2 ), vanadium oxide, Ni-site type lithium nickel oxide, lithium manganese composite oxide, lithium manganese composite oxide with spinel structure, LiMn 2 O 4 , disulfide compound, Fe 2 (MoO 4 ) 3 8. The method for manufacturing an electrode for a secondary battery according to claim 7, wherein the electrode comprises at least one of the following:
11. A secondary battery comprising the electrode for a secondary battery according to claim 1.
Citation Information
Patent Citations
Dry electrode for energy storage device and its manufacturing method
JP2017517862A
Binder for secondary battery, cathode and secondary battery including binder
KR1020140099715A
Positive electrode, lithium secondarty battery comprising the positive electrode, and method for manufacturing the positive electrode
KR1020180121411A